Effects of lycopene against cisplatin-induced nephrotoxicity and oxidative stress in rats - Atessahin, A; Yilmaz, S; Karahan, I; Ceribasi, AO; Karaoglu, A (Elsevier Ireland Ltd, 2005)
The aim of this study was to investigate the effects of lycopene on cisplatin-induced nephrotoxicity and oxidative stress in rats. Adult male Sprague-Dawley rats were randomly divided into four groups. The control group (group 1) received physiological saline; animals in group 2 received only cisplatin; a 10 days of lycopene pre-treatment was applied to the animals in group 3 before administration of cisplatin; a 5 days of lycopene treatment was performed following administration of cisplatin for the animals in group 4. Cisplatin (7 mg/kg) was intraperitoneally injected as a single dose and lycopene (4 mg/kg) was administered by gavage in corn oil. Biochemical and histopathological methods were utilised for evaluation of the nephrotoxicity. The concentrations of creatinine, urea, Na+ and K+ in plasma and levels of malondialdehyde and reduced glutathione as well as glutathione peroxidase and catalase activities were deter-mined in kidney tissue. Administration of cisplatin to rats induced a marked renal failure, characterized with a significant increase in plasma creatinine and urea concentrations. Na+ and K+ levels of rats received cisplatin alone were not significantly different compared to control group, but they had higher kidney malondialdehyde, and lower reduce glutathione concentrations, glutathione peroxidase and catalase activities. Lycopene administration produced amelioration in biochemical indices of nephrotoxicity in both plasma and kidney tissues when compared to group 2; pre-treatment with lycopene being more effective. Results from this study indicate that the novel natural antioxidant lycopene might have protective effect against cisplatin-induced nephrotoxicity and oxidative stress in rat. (c) 2005 Elsevier Ireland Ltd. All rights reserved.
Keywords: cisplatin; lycopene; lipid peroxidation; antioxidants; histopathology